2012
DOI: 10.1002/ijc.27892
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin‐6 level is a prognostic marker for survival in advanced nonsmall cell lung cancer patients treated with chemotherapy

Abstract: Lung cancer is the leading cause of cancer death worldwide as well as in Taiwan. Interleukin-6 (IL-6) is a multifunctional cytokine and has been implicated in tumor progression. This study recruited 245 patients with advanced (Stage 3B/4) nonsmall cell lung cancer (NSCLC) that had received chemotherapy, to evaluate associations between IL-6 and lung cancerspecific survival. Among these subjects, 112 gave blood samples before and 133 after the start of chemotherapy. Plasma IL-6 was measured using an enzyme link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
121
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(133 citation statements)
references
References 37 publications
8
121
1
3
Order By: Relevance
“…IL-6 is known to directly promote tumour growth, but also facilitates immune invasion by several signalling pathways, in particular the signal transducer and transcription activator 3 [36]. Moreover, IL-6 might not only be induced by chemotherapy, but also mediate therapy resistance, which could add to the worse prognosis of patients with high circulating IL-6 levels [38]. Interestingly, in a former study by our group, enhanced levels of C-reactive protein (CRP), an acute-phase protein known to be induced strongly by IL-6, indicated a worse prognosis of cancer patients not associated with VTE frequency [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-6 is known to directly promote tumour growth, but also facilitates immune invasion by several signalling pathways, in particular the signal transducer and transcription activator 3 [36]. Moreover, IL-6 might not only be induced by chemotherapy, but also mediate therapy resistance, which could add to the worse prognosis of patients with high circulating IL-6 levels [38]. Interestingly, in a former study by our group, enhanced levels of C-reactive protein (CRP), an acute-phase protein known to be induced strongly by IL-6, indicated a worse prognosis of cancer patients not associated with VTE frequency [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already shown that elevated levels of IL-6 correlated with lower survival rates [30,43] of cancer patients, including those of metastatic breast cancer [44], gastrointestinal cancer [28], metastatic renal cell carcinoma [29] prostate cancer [45] and lung cancer [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If cancer cells increasingly secrete IL-6, it may act in an autocrine manner to enhance the metastatic ability (17) and resistance of the tumor to treatment (18). The increased levels of IL-6 have been correlated with poor prognosis and survival rate in a variety of types of cancer (19)(20)(21)(22). Previous studies on solid tumors, including gastric, renal cell, colorectal, prostate, non-small cell lung, melanoma and head and neck cancer and hematologic malignancies, including myeloma and non-Hodgkin's lymphoma, have indicated the potential prognostic significance of IL-6 levels (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Vrlo retko su u istraživanjima uključene obe grupe bolesnika s karcinomom pluća. Chang i suradnici su istraživali vrednosti IL6 u uzorcima seruma iz SCLC i sva tri oblika NSCLC (19). Oni su pokazali da povećanje IL6 je povezano s brzim napretkom bolesti i lošim odgovorom na terapiju kod svih bolesnika sa LC.…”
unclassified